Methods of analysis applied on the e-shop Arsta - Flégl, Jan (2014)
Bachelor thesis is focused on summarizing methods of e-shop analysis. The first chapter summarizes and describes the basics of e-commerce and e-shops in general. The second chapter deals with search engines, their functioning and in what ways it is possible to influence the order of search results. Special attention is paid to the optimization and search engine marketing. The third chapter summarizes basic tools of the Google Analytics. The fourth chapter uses findings of all the previous chapters, when analyzing the e-shop Arsta. The aim of this thesis is to explore various methods by which it is possible to evaluate and analyze the performance of e-shop and also to suggest directions to improve the current situation.